Perception of Senior High School Teachers Towards School Organization Support - Rosita Endang Kusmaryani; Juke R Siregar; Hanna Widjaja; Ratna Jatnika (LPMPP Universitas Negeri Yogyakarta, 2017)
Abstract: The purpose of this study is to explore the forms of teacher’s Perceived School Organizational Support. This quantitative study was carried out based on a survey in the form of open questionnaire that allowed research subjects to answer freely. The subjects in this study were 97 high school teachers from four schools in Bantul and one school in the Municipality of Yogyakarta. They were selected through multistage cluster random. Data were analyzed using quantitative analysis, particularly that of percentage technique. It can be synthesized from the results of this study that (1) teacher’s Perceived School Organizational Support has four-dimensions which encompass convenient physical work environment (41%), professional development (27%), attention from the leaders (18%) and comfortable social work environment (14%); and (2) the emotional responses toward School Organizational Support are various, such as feeling happy, satisfied, better, and motivated, working comfortably, increasing work motivation, possessing positive thinking, as well as believing in self-development. Keywords: school organizational support, professional development PERSEPSI GURU SMA NEGERI TERHADAP DUKUNGAN ORGANISASI SEKOLAH Abstrak: Tujuan penelitian ini adalah untuk mengeksplorasi bentuk-bentuk dukungan organisasi sekolah yang dirasakan (Perceived School Organization Support) oleh guru. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian survei. Subjek berjumlah 97 orang guru SMU yang terdiri atas 4 sekolah mewakili Kabupaten Bantul dan 1 sekolah mewakili Kodya Yogyakarta. Pemilihan subjek penelitian dilakukan dengan melalui teknik multistage cluster random. Pengumpulan data dilakukan melalui angket terbuka yang memungkinkan subjek penelitian menjawab secara bebas. Validitas angket diperoleh lewat professional judgment. Data dianalisis menggunakan analisis kuantitatif dengan teknik persentase. Hasil penelitian ini menemukan bahwa: (1) empat dimensi dukungan sekolah yang merupakan bentuk-bentuk dukungan organisasi sekolah yang dirasakan guru antara lain kenyamanan lingkungan fisik kerja (41%), pengembangan profesi (27%), perhatian pimpinan (18%), dan kenyamanan lingkungan sosial kerja (14%); (2) respon emosi yang muncul dengan adanya dukungan sekolah antara lain senang, puas, nyaman bekerja, menambah semangat kerja, positive thinking terhadap sekolah, perasaan mampu mengembangkan diri, termotivasi, merasa sejahtera, dan merasa dihargai. Kata kunci: dukungan organisasi sekolah, pengembangan profesional